The Effect Of Export And Development Spending On Indonesia's Economic Growth - Kosali, Ahmad Yani (FEB Universitas Sultan Ageng Tirtayasa, 2024)
Economic growth is a significant increase in national income within a certain calculation period. This study aims to analyze the effect of exports and development spending on Indonesia's economic growth, as well as which variables have the dominant influence on Indonesia's economic growth. The data used in this study is secondary 10-year time series data between 2013-2022. Data were obtained from various sources, including the Central Bureau of Statistics (BPS), and scientific journals and other literature related to this research topic. The analytical method used in this study is multiple regression analysis which is used to determine the magnitude of the effect of changing one variable on another variable with the help of SPSS 22. From the regression results above the value of R squared (R2) is 0.957, this means 95.7% variation changes in economic growth variables can be explained simultaneously by variations in export and development expenditure variables, the remaining 4.3% is determined by other variables or factors outside the model. For exports, the results of the study show a significance value lower than the significant level (0.000 <0.05) so that Ho is rejected, Ha is accepted, thus exports have a positive and significant effect on economic growth. While development expenditure, the significant value is greater than the significance level (0.251 > 0.05) so that Ho is accepted Ha is rejected thus the results of the study show that the coefficient of development expenditure (x2), is not significant to Indonesia's economic growth. The Indonesian government must pay attention to the role of exports, which significantly have a positive influence on national income. Indonesia's exports are still dominated by primary products or raw materials and the lack of infrastructure and superstructure support is an obstacle to increasing Indonesia's export productivity. Therefore, good coordination between economic actors and monetary policy makers is needed so that the budget policies adopted will not disrupt monetary stability and vice versa.